2007
DOI: 10.1007/s10533-007-9103-5
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of organo-mineral interactions in soils: self-assembly of organic molecular fragments into zonal structures on mineral surfaces

Abstract: In this paper, we propose a structure for organo-mineral associations in soils based on recent insights concerning the molecular structure of soil organic matter (SOM), and on extensive published evidence from empirical studies of organo-mineral interfaces. Our conceptual model assumes that SOM consists of a heterogeneous mixture of compounds that display a range of amphiphilic or surfactant-like properties, and are capable of self-organization in aqueous solution. An extension of this self-organizational beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
770
5
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 992 publications
(839 citation statements)
references
References 106 publications
(127 reference statements)
59
770
5
5
Order By: Relevance
“…In this context, it is worth noting that Kleber et al (2007) found INA protein complexes to be well preserved -and maybe accumulated -when being connected to mineral surfaces. Also Conen et al (2011) found that organic matter consisting of remains of micro-organisms that took part in the degradation of plant debris is responsible for enhancing the ice nucleation of atmospheric mineral dust.…”
Section: Discussionmentioning
confidence: 91%
“…In this context, it is worth noting that Kleber et al (2007) found INA protein complexes to be well preserved -and maybe accumulated -when being connected to mineral surfaces. Also Conen et al (2011) found that organic matter consisting of remains of micro-organisms that took part in the degradation of plant debris is responsible for enhancing the ice nucleation of atmospheric mineral dust.…”
Section: Discussionmentioning
confidence: 91%
“…The composition of plant tissues is a major factor influencing the process of their decomposition and soil carbon incorporation in temperate ecosystems (Kögel-Knabner 2002;Kleber et al 2007). The soil organic carbon may reside in more labile or stable organic matter according to the chemical composition and recalcitrance of plant residues (Berg & McClaugherty 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in FGS, at a higher stability of HA the carbon content in the aggregates is higher, too. Here the HS create bonds with clay minerals, they are not only adsorbed on their surfaces, but also can penetrate into clay interlayers (Kleber et al 2007). In FGS, aromatic carbon components are dominant in organic structures (Jindaluang et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The fine frac-doi: 10.17221/31/2017-SWR tions (clay, silt) are in a positive correlation with total organic carbon (TOC) and the coarse fractions (sand) in a negative (Burke et al 1989;Bronson et al 2004). A significant part of clay minerals is in the linkage with a large amount of organic substances (Jastrow 1996), which can be stabilized through the adsorption on the mineral surfaces (Baldock & Skjemstad 2000), bridges of polyvalent cations (Muneer & Oades 1989), binding into the interlayers of clay minerals (Kleber et al 2007). The stabilization of SOM is mainly controlled by the organo-mineral association (Cai et al 2016) and the iron-oxides and hydroxides.…”
mentioning
confidence: 99%